Jual Beli Lelang di Akun Instagram Hype Auction Perspektif Etika Bisnis Islam - Turmudi, Imam (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Buying and selling has been done by humans for a long time. Islam prescribes buying and selling as a way to meet life’s needs through fair means. As time goes by, the practice of buying and selling is increasingly developing with a shift from tangible places, now it can be done in places that are not tangible. The aim of this research is to describe buying and selling via the Hype Auction Instagram account from the perspective of Islamic business ethics. Research was not conducted on all social media users, so researchers need a sample that can represent the data needed. The samples taken into consideration by researchers were social media users who the author already knew and could meet directly. In this case, the researcher took several samples based on these considerations, and then the data results were analyzed using inductive analysis. Analysis of the practice of buying and selling via social media shows that both the concepts of unity, balance, freedom, responsibility and virtue, it can be seen that there are still buying and selling actions that have not fulfilled the conditions, then sellers still hide defects in the goods being sold, forced purchases of goods also occur. by some buyers. The results of this research explain that the practice of buying and selling via social media is not in accordance with Islamic business ethics.